Case Series of Phthirus pubis Infestation in Non-Perineal Regions - Nie J; Shen X; Li Y; Wang W (Dove Medical Press, 2023)
Jing Nie, Xue Shen, Yan Li, Wenju Wang Department of Dermatology, Chengdu Second People's Hospital, Chengdu, Sichuan, 610000, People's Republic of ChinaCorrespondence: Jing Nie, Department of dermatology, Chengdu Second People's Hospital, 165 Caoshi Street, Qingyang District, Chengdu, Sichuan, 610000, People's Republic of China, Tel +86-15902687253, Email niejing122402@163.comAbstract: Pediculosis has been reported in all countries and socio-economic classes. Due to the small size and translucent nature of their nits, patients with Pthirus pubis may be misdiagnosed. Here, we report three cases of Pthirus pubis infection involving different body sites, including the eyelashes, axillary region and head, respectively. This case series have discussed their clinical features and corresponding responses. A large number of eggs and adult pubic lice were observed under dermoscopic observation, which can be considered an effective tool for diagnosing Pthirus pubis and reducing the misdiagnosis rate.Keywords: Phthirus pubis, eyelashes, axillary region, head, dermoscopy